Volar Central Portal in Wrist Arthroscopy - Corella, F. (J Wrist Surg, 2016)
Background Nowadays, the wrist is not limited to a dorsal visualization; the joint can be thought of as a “box,” which can be visualized from almost every perspective. The purpose of this study was to describe a new volar central portal for the wrist, following three principles: a single incision that allows access to both the radiocarpal and midcarpal joints, centered on the lunate, with the volar structures at risk protected not only by retractors, but also by tendons. Description of Technique The incision begins in the distal wrist crease and extended 1.5 cm proximally up to the proximal wrist crease, following the axis of the third intermetacarpal space. The flexor superficialis tendons are identified and retracted toward the radial side. Next, the fourth and fifth flexor digitorum profundus tendons are retracted toward the ulnar side, while the third and second tendons are retracted toward the radial side. The volar central midcarpal portal is performed under direct vision just over the anterior horn of the lunate through the Poirier space. The volar central radiocarpal portal is created under the lunate through the interval between the ulnocarpal ligaments and the short radioulnar ligament. Methods An anatomical study was performed on 14 cadaver specimens. Two data were recorded: iatrogenic injuries of the structures at risk and the distances to the structures at risk. Results The median (interquartile range [IQR]) distances from the volar central radiocarpal portal to the median nerve, palmar cutaneous branch of the median nerve, and ulnar neurovascular bundle were 10.5 (7.8–15.0), 18.5 (15.8–20.3), and 7.0 (5.0–10.5) mm, respectively. The median (IQR) distances from the volar central midcarpal portal to the median nerve, palmar cutaneous branch of the median nerve, and ulnar neurovascular bundle were 7.0 (4.8–10.3), 16.0 (14.8–19.0), and 4.5 (3.8–9.0) mm, respectively. No iatrogenic injuries were observed. Conclusion The volar central portal is reproducible and safe. The risk of iatrogenic injury is low. The capsule is pierced through one of its thinner portions, and both the radiocarpal and midcarpal joints can be inspected through one single incision.